PERLINDUNGAN HUKUM PROFESI BIDAN DALAM PELIMPAHAN WEWENANG TINDAKAN MEDIS - Lastini, Ketut; Sutrisno, Endang; Sugiarti, Taty (Faculty of Law, Universitas 17 Agustus 1945 Surabaya, 2020)
AbstractMedical actions taken by the midwife and cause medical problems, will potentially lead to lawsuits, if the Midwife does not carry out the transfer of authority in accordance with statutory regulations. The problem is how the form of legal protection for the midwife profession in connection with the delegation of authority in carrying out medical actions, this is intended to examine the form of legal protection, with a normative juridical research approach. The delegation of authority for medical actions is regulated in various regulations. In reality, in daily practice, there are hospitals that have not yet managed the technical operational aspects regarding the delegation of authority over medical procedures, how the mechanism for delegating authority, or what types of medical actions can be delegated or delegated. Juridical consequences if there are allegations of abuse of authority can lead to civil and criminal lawsuits.Keywords: delegation of authority; medical treatment; midwifeAbstrakTindakan medis yang dilakukan oleh bidan dan menimbulkan masalah medis,akan berpotensi terjadinya tuntutan hukum, jika Bidan tidak melaksanakan pelimpahan wewenang sesuai dengan peraturan perundang-undangan. Persoalannya bagaimanakah bentuk perlindungan hukum profesi bidan sehubungan dengan pelimpahan wewenang dalam melaksanakan tindakan medis, hal ini dimaksudkan untuk menelaah bentuk perlindungan hukumnya, dengan pendekatan penelitian yuridis normatif. Pelimpahan wewenang tindakan medis sudah diatur dalam berbagai regulasi. Kenyataan dalam praktek sehari-hari, masih ada rumah sakit yang belum mengatur secara teknis operasional tentang pelimpahan wewenang tindakan medis, bagaimana mekanisme pelimpahan wewenang, maupun jenis-jenis tindakan medis apa saja yang bisa dilimpahkan secara delegasi maupun mandat. Konsekuensi yuridis jika ada dugaan penyalahgunaan wewenang dapat menimbulkan gugatan perdata maupun pidana.Kata kunci: bidan; pelimpahan wewenang; tindakan medis